Opposite gene by environment interactions in Karelia for CD14 and CC16 single nucleotide polymorphisms and allergy - Zhang, Guicheng; Khoo, S.; Laatikainen, T.; Pekkarinen, P.; Vartiainen, E.; Von Hertzen, L.; Hayden, C.; Goldblatt, J.; Mäkelä, M.; Haahtela, T.; Le Souëf, P. (2009)
Background: Finnish Karelians have a higher prevalence of allergic disease than Russian Karelians. As both populations are generally from the same ethnic group, the Karelian population offers a unique opportunity to analyse genetic and allergic disease interactions between 'Western' and 'Eastern' environments. Objectives: We investigated associations between allergic diseases and CD14 and CC16 polymorphisms in Finnish vs Russian Karelian women. Methods: Adult female Karelians (330 Finnish and 274 Russian) were recruited, examined for a range of symptoms and conditions including rhinitis, itchy rash, asthma and atopy and genotyped for CD14 C-159T and CC16 A38G. Results: For both CD14 C-159T and CC16 A38G, the risk allele for atopic phenotypes in Finnish Karelia was the protective allele in Russian Karelia. For CD14 C-159T, an interactive effect on ever itchy rash (Pinteraction = 0.004), itchy rash <12 mo (P interaction = 0.001) and dry cough at night in the past 12 months (<12 months) (Pinteraction = 0.011) was found; the risk allele was C in Russians and T in Finns. For CC16 A38G, an interaction was significant for ever rhinitis (Pinteraction = 0.006), rhinitis <12 mo (P interaction = 0.004), and marginally significant for ever hayfever (Pinteraction = 0.07), allergic eye symptoms <12 mo (P interaction = 0.09); their risk allele was G in Russians and A in Finns. Conclusion: An Eastern vs Western environment appears to exert an effect via opposite alleles on risk of allergic diseases in adult women. © 2009 John Wiley & Sons A/S.